2022
DOI: 10.3389/fvets.2022.883389
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diversity of Antimicrobial Resistance Phenotypes and Genotypes of Mannheimia haemolytica Isolates From Bovine Nasopharyngeal Swabs

Abstract: The threat of bovine respiratory disease (BRD) for cattle operations is exacerbated by increasing prevalence of antimicrobial resistance (AMR) in Mannheimia haemolytica, a leading cause of BRD. Characterization of AMR in M. haemolytica by culture and susceptibility testing is complicated by uncertainty regarding the number of colonies that must be selected to accurately characterize AMR phenotypes (antibiograms) and genotypes in a culture. The study objective was to assess phenotypic and genotypic diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The selection of only one MH colony for some analyses may be considered a limitation of the present study. However, in 2022, Carter et al showed that there was little phenotypic or genotypic variation in MH colonies isolated from NPS from an individual animal, and MICs differed by only one dilution factor when differences occurred ( 59 ); therefore, we considered the selection of only one colony for AST and WGS acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of only one MH colony for some analyses may be considered a limitation of the present study. However, in 2022, Carter et al showed that there was little phenotypic or genotypic variation in MH colonies isolated from NPS from an individual animal, and MICs differed by only one dilution factor when differences occurred ( 59 ); therefore, we considered the selection of only one colony for AST and WGS acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also identified that calves have the potential to simultaneously shed P. multocida isolates with differing plasmid profiles [30]. Together, these studies indicate that while a dominant strain of bacteria might exist within a sample, the present study could have missed resistant isolates if only one colony per plate was selected for testing, particularly in the case of H. somni, for which the diversity of isolates within individual plates has not been evaluated [65,67].…”
Section: Study Limitationsmentioning
confidence: 70%
“…The number of colonies needed to estimate the diversity of isolates present on a primary culture plate has been determined for other bacterial pathogens [64]. To investigate this question in reference to M. haemolytica and describe the potential phenotypic and genotypic diversity of M. haemolytica isolates from individual animals, Carter et al collected DNP swabs from 28 cattle at risk of, or treated for, BRD [65]. Up to 20 M. haemolytica colonies were selected per plate (up to 100 colonies per nasopharyngeal swab) [65].…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations